Social Science Applications in Sustainable Aviation Biofuels Research: Opportunities, Challenges, and Advancements - Anderson, Brian J.; Mueller, Daniel W.; Hoard, Season A.; Sanders, Christina M.; Rijkhoff, Sanne A. M. (Frontiers in Energy Research, 2022)
Social science has an important role in aviation biofuels research, yet social science methods and approaches tend to be underdeveloped and under-utilized in the broader aviation biofuels literature and biofuels overall. Over the last 5 years, social science approaches in aviation biofuels research, particularly site-selection, have made several advances. Where early site-selection models either entirely excluded social science concepts or included only a few measurements using poor proxies, current models more accurately, and more comprehensively capture key social science concepts to better examine and predict project implementation success and long-term sustainability. Despite several studies published within the last 20 years noting the need for more empirical studies of social sustainability and improvement in incorporation of social criteria, progress has remained rather stagnant in several areas. To help move the field forward, we conduct a review of the current state of social science research in aviation biofuels with a focus on sustainability, site-selection, and public acceptance research, identifying key approaches, important developments, and research gaps and weaknesses of current approaches. While several review studies already exist, they tend to focus on a single area of biofuels such as public acceptance. By broadening our review to several areas, we are able to identify several common limitations across these areas that contribute to the continued underutilization of social science approaches in aviation biofuels. This includes the preference for practical and reliable indicators for social criteria that prioritize quantitative methods over other approaches. Based on these limitations, we make several recommendations to improve social science research in aviation biofuels, including ensuring that social scientists are key members of the research team, the adoption of a mixed-methods research designs that combines quantitative and qualitative approaches that better measure some criteria and local-level impacts, and adequate resources for social science research throughout biofuel development projects as these methods are often more time-consuming and costly to implement. We argue that implementing these recommendations in future aviation biofuel development projects will improve social science approaches utilized in aviation biofuels research and address a long-acknowledged gap in the field.